(untitled) (Fiep Bulletin - online, 2014)
Brazil is a major consumer of drugs, but there is a clear imbalance in the domestic market. Millions of citizens have no access to drug treatment and those who consume, the expired and unexpired medicines remains are notorious. This table associated with the lack of specific legislation on the disposing, collection, transportation and destination of household waste medicines, has caused contamination of water and soil by pharmaceuticals. These reasons justify the need to recognize the attitudes of the population regarding the disposing of household medicines. Questionnaires were given to representatives of 102 households in the city of Petrópolis-RJ. It was found that the disposing of drugs is mostly done improperly, regardless of age or level of education and lack of knowledge about fractionated sales these drugs leads to leftovers after treatment. Certainly, the establishment of clear rules on the subject, combined with awareness campaigns would have great impact on this dangerous context.